Reverse-phase-structure nickel-based catalyst for water-gas shift reaction as well as preparation method and application of reverse-phase-structure nickel-based catalyst
The reverse-phase structure nickel-based catalyst prepared by a one-step hydrothermal method uses the ratio control and accelerator of nickel salt and cerium salt to form a catalyst with high activity, thermal stability and good redox resistance, which solves the existing CO transformation catalyst. The problems of low activity and poor stability in fuel cells have achieved excellent water vapor conversion reaction performance under non-steady conditions.
Patent Information
- Application Number
- CN202411643528.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
AI Technical Summary
The existing CO conversion catalysts are low in activity, poor thermal stability, weak redox atmosphere impact resistance and short life in fuel cell hydrogen source systems that operate non-steady state, so they cannot be effectively applied in fuel cells.
The reverse-phase structure nickel-based catalyst is prepared by one-step hydrothermal method. Through strict ratio control of nickel salt and cerium salt, combined with promoters such as ethylene glycol, acetic acid, propionic acid, etc., a uniformly distributed interface between cerium dioxide and nickel oxide is formed to improve the Catalyst activity, stability and redox resistance.
It significantly improves the activity, thermal stability and life of the catalyst, and exhibits excellent water vapor transformation reaction activity and stability under high aerial speed and non-steady conditions, solving the insufficient application of traditional catalysts in fuel cells.
Smart Images

Figure CN119259062A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and more specifically relates to a reverse-phase nickel-based catalyst for water-gas shift reaction, and a preparation method and application thereof. Background Art
[0002] Hydrogen energy (hereinafter referred to as hydrogen energy) is a renewable, clean and efficient secondary energy source with many advantages such as abundant resources, wide sources, high combustion calorific value (120.7KJ / g), clean and pollution-free, diverse forms of use, can be used as an energy storage medium and good safety. It is an important energy source for achieving energy transformation and carbon neutrality. However, the current development of hydrogen energy is still limited. On the one hand, the activity and life of the catalyst for preparing hydrogen energy still need to be improved. On the other hand, hydrogen itself is a flammable and explosive gas, and there is currently no safe and cheap hydrogen storage technology.
[0003] The development of hydrogen energy is inseparable from fuel cells. At present, fuel cells produce CO in the reforming stage of hydrogen production, which deactivates fuel cell catalysts and thus affects the practical application of fuel cells. The water gas shift reaction (WGS) can not only reduce the CO content in hydrogen, but also produce the same volume of hydrogen, which is the main method to solve the above problems. In addition, as a hydrogen supply system for fuel cells, the hydrogen production process will be a non-steady-state process. Therefore, the catalyst used in this process must not only adapt to the temperature changes and changes in the redox atmosphere caused by different working conditions such as start-up, load change, and shutdown, but also have sufficient stability and life. Traditional CO shift catalysts are generally divided into low-shift (represented by Cu-Zn-Al catalysts, with an operating temperature of 180-280°C) catalysts and high-shift (represented by Fe-Cr catalysts, with an operating temperature of 350-450°C) catalysts. They are mainly used in steady-state industrial processes with strictly controlled operating conditions. After reduction, they will spontaneously ignite when encountering air, causing the active components of the catalyst to sinter and deactivate. Therefore, these two types of shift catalysts cannot be used in non-steady-state fuel cell hydrogen source systems.
[0004] Therefore, developing a CO conversion catalyst with high activity, good thermal stability, resistance to redox atmosphere shock and long life has become one of the keys to fuel cell hydrogen source technology. Summary of the invention
[0005] The purpose of the present invention is to provide a reverse-phase structure nickel-based catalyst for water gas shift reaction and its preparation method and application, so as to solve the problems existing in the above-mentioned prior art, achieve a significant improvement in the activity, thermal stability, resistance to redox atmosphere impact and life of the CO shift catalyst, and ensure that the CO shift catalyst can be used in a fuel cell hydrogen source system operating in a non-steady-state state.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a reverse phase structure nickel-based catalyst for water gas shift reaction, comprising the following steps:
[0008] Mixing cerium salt, nickel salt, promoter and water to obtain a mixed solution; subjecting the mixed solution to hydrothermal treatment and drying in sequence to obtain a solid product; calcining the solid product to obtain the reverse phase structure nickel-based catalyst;
[0009] The promoter includes one or more of ethylene glycol, acetic acid, propionic acid and ethanol.
[0010] The present invention adopts a one-step hydrothermal method to prepare a reverse-phase structure nickel-based catalyst, which includes a nickel salt, a cerium salt and a promoter, wherein the promoter is selected from one or more of ethylene glycol, acetic acid, propionic acid and ethanol. The nickel salt is treated to form a compound containing nickel elements, which constitutes an active component in the reverse-phase structure nickel-based catalyst; the cerium salt is treated to form an oxide cerium dioxide, which constitutes a carrier in the reverse-phase structure nickel-based catalyst. The present invention strictly controls the addition ratio of nickel salt and cerium salt and the loading amount of oxide on the carrier surface, thereby ensuring that cerium dioxide is uniformly dispersed on the surface of the compound containing the nickel element, and prepares a reverse-phase structure nickel-based catalyst with ideal structure (nickel oxide is uniformly distributed around spherical cerium dioxide to form a nickel-cerium dioxide interface) and high catalytic conversion rate; the promoter is selected from one or more of ethylene glycol, acetic acid, propionic acid and ethanol, and the promoter mainly plays the following roles in the preparation process of the reverse-phase structure nickel-based catalyst: (1) as a solvent and pH value regulator: to promote the dissolution and reaction degree of each raw material in the preparation process of the reverse-phase structure nickel-based catalyst; (2) as a stabilizer: to enhance the stability of the reverse-phase structure nickel-based catalyst and avoid the inactivation or decomposition of the reverse-phase structure nickel-based catalyst during the reaction. In addition, the ethylene glycol in the promoter can also be used as an efficient coolant to ensure the stability of the inverse structure nickel-based catalyst in high temperature reactions; (3) Enhance the catalytic activity, selectivity and stability of the inverse structure nickel-based catalyst: The promoter can improve the catalytic activity of the inverse structure nickel-based catalyst, and can also enhance the activity and selectivity of the catalytic reaction, and promote the smooth progress of the catalytic reaction; the acetic acid in the promoter can form a complex with the metal ions, thereby enhancing the activity of the metal ions; this complex helps to improve the catalytic efficiency of the catalyst during the preparation of the catalyst, and significantly improves the catalytic reaction rate, selectivity and stability; (4) Optimize the reaction conditions in the preparation of the inverse structure nickel-based catalyst: When acetic acid is used as a promoter, the interaction between the carboxyl and methyl groups in its molecular structure can promote the interaction between the reactants, thereby optimizing the reaction conditions and improving the reaction efficiency in the preparation of the inverse structure nickel-based catalyst. In addition, the ethylene glycol in the promoter can promote the growth and crystallization of cerium dioxide particles, and the prepared cerium dioxide has good dispersibility, stable lattice and good catalytic performance.
[0011] The inverse-phase structure nickel-based catalyst prepared by the present invention has the characteristics of high activity, good thermal stability, resistance to redox atmosphere shock and long life. Under high space velocity and non-steady-state conditions, it shows better water vapor shift reaction activity and stability than industrial catalysts. It solves the problems existing in the existing CO shift catalyst commonly used in water vapor shift reaction.
[0012] Preferably, the cerium salt includes cerium nitrate and / or cerium acetate; and the nickel salt includes nickel nitrate and / or nickel acetate.
[0013] Preferably, the molar ratio of the cerium salt to the nickel salt is 1-9:1-9; the concentration of the cerium salt in the mixed solution is 6.32-75.94 g / L; the volume ratio of the accelerator to water is 15-16:0.5-1;
[0014] When the molar ratio of nickel salt to cerium salt exceeds the upper limit of the specified range, nickel oxide increases and agglomerates, resulting in a decrease in catalytic performance; when the molar ratio of nickel salt to cerium salt is lower than the lower limit of the specified range, cerium dioxide increases and the catalytic performance decreases.
[0015] Preferably, the temperature of the hydrothermal treatment is 170-190° C., and the time of the hydrothermal treatment is 5-7 hours.
[0016] Preferably, the drying time is 11 to 13 hours.
[0017] Preferably, the calcination temperature is 480-520° C., the calcination time is 3.5-4.5 h, and the calcination heating rate is 8-12° C. / min.
[0018] More preferably, the step of centrifugation is further included before drying.
[0019] The second technical solution of the present invention: provides a reversed-phase structure nickel-based catalyst prepared by the preparation method of the reversed-phase structure nickel-based catalyst for water gas shift reaction, wherein the active component in the reversed-phase structure nickel-based catalyst is a compound containing nickel element, and the carrier is cerium dioxide.
[0020] The third technical solution of the present invention is to provide the application of the reverse phase structure nickel-based catalyst in water vapor exchange reaction.
[0021] Preferably, the reaction conditions of the water vapor exchange reaction are: the pressure is normal pressure, the temperature is 150-400°C, the reaction gas is a mixed gas composed of CO, water and inert gas, and the feed space velocity of the mixed gas is 41000-43000h -1 .
[0022] More preferably, the inert gas includes argon or nitrogen; in the mixed gas consisting of CO, water and the inert gas, the volume proportion of CO is 1-3%, the volume proportion of water is 8-12%, and the rest is the inert gas.
[0023] Preferably, the reverse structure nickel-based catalyst is subjected to reduction treatment before the water vapor exchange reaction; the reduction treatment comprises: reducing the reverse structure nickel-based catalyst with a mixed gas of H2 and Ar; the volume proportion of H2 in the mixed gas of H2 and Ar is 10-50%; the temperature of the reduction treatment is 450-550°C, and the time of the reduction treatment is 1-1.5h.
[0024] The present invention discloses the following technical effects:
[0025] The catalyst preparation process of the present invention is simple and easy to operate. Specifically, the present invention adopts a one-step hydrothermal method to prepare a reversed-phase structure nickel-based catalyst, which does not require other complex preparation processes, is easy to industrialize and mass-produce, has a low product cost, and has good industrial application prospects. In the reversed-phase structure nickel-based catalyst prepared by the present invention, cerium dioxide is well dispersed on a nickel metal carrier. Under high space velocity and non-steady-state conditions, it exhibits more excellent water vapor shift reaction activity and stability than industrial catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The X-ray diffraction patterns of the catalysts obtained in Examples 1 to 4 and Comparative Example 3;
[0027] Figure 2 is a SEM image of the catalyst obtained in Example 5;
[0028] Figure 3 The figure is a relationship diagram of the catalytic activity of the catalysts obtained in Examples 1 to 4 and Comparative Examples 1 to 3, i.e., the conversion rate of CO as a function of temperature;
[0029] Figure 4 This is a stability evaluation of the catalyst obtained in Example 5, i.e. a relationship diagram of the CO conversion rate changing with the catalytic time. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The raw materials used in the following examples, comparative examples and performance tests are all commercially available unless otherwise specified; the normal pressure represents 0.1013 MPa unless otherwise specified.
[0036] Example 1
[0037] (1) Weigh 6 g Ce(NO3)2·6H2O and 0.445 g Ni(NO3)2·6H2O (the molar ratio of nickel salt to cerium salt is 1:9) and dissolve them in 8 mL deionized water;
[0038] (2) acetic acid (2 mL) and ethylene glycol (156 mL) were added and stirred vigorously to form a homogeneous solution;
[0039] (3) The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and subjected to hydrothermal treatment at 180 °C for 6 h;
[0040] (4) Afterwards, the precipitate was washed and separated by centrifugation, and the precipitate was dried at 80° C. overnight (12 h);
[0041] (5) The solid obtained after drying was calcined in a muffle furnace at 500° C. for 4 h at a heating rate of 10° C. / min to obtain a Ni1Ce9 catalyst.
[0042] Example 2
[0043] The difference from Example 1 is: the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 12 g and 3.444 g respectively, ensuring that the molar ratio of nickel salt to cerium salt is 3:7. The rest is the same as Example 1, and a Ni3Ce7 catalyst is obtained.
[0044] Example 3
[0045] The difference from Example 1 is: the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 9 g and 6.0273 g respectively to ensure that the molar ratio of nickel salt to cerium salt is 5:5. The rest is the same as Example 1 to obtain a Ni5Ce5 catalyst.
[0046] Example 4
[0047] The difference from Example 1 is that the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 3 g and 4.68881 g respectively to ensure that the molar ratio of nickel salt to cerium salt is 7:3. The rest is the same as Example 1 to obtain a Ni7Ce3 catalyst.
[0048] Example 5
[0049] The difference from Example 1 is that the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 1 g and 6.0275 g respectively to ensure that the molar ratio of nickel salt to cerium salt is 9:1. The rest is the same as Example 1 to obtain a Ni9Ce1 catalyst.
[0050] Figure 1 The X-ray diffraction patterns of the catalysts obtained in Examples 1 to 5 are shown in FIG. Figure 2 This is a SEM image of the catalyst obtained in Example 5. Figure 1 It can be seen that the X-ray diffraction pattern of the reverse phase structure nickel-based catalyst prepared in the example contains obvious characteristic peaks of CeO2 and NiO. Figure 2 It can be seen that in the catalyst obtained in Example 5, nickel oxide is evenly distributed around the spherical ceria to form a nickel-ceria interface, which proves that the present invention successfully prepares a reverse-phase structure nickel-based catalyst.
[0051] Comparative Example 1
[0052] The difference from Example 4 is that the addition of Ni(NO3)2·6H2O is omitted, and the rest is the same as Example 4 to obtain a CeO2 catalyst.
[0053] Comparative Example 2
[0054] 10 g Ni(NO3)2·6H2O was calcined at 500°C for 4 h with a heating rate of 10°C / min to obtain a single nickel catalyst.
[0055] Comparative Example 3
[0056] The difference from Example 4 is that the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 14 g and 0.85232 g respectively, and the molar ratio of nickel salt to cerium salt is ensured to be 1:11. The other steps are the same as those in Example 4 to obtain Ni1Ce 11 catalyst.
[0057] The Ni1Ce obtained in this comparative example 11 The amount of spherical cerium dioxide in the catalyst increases, the oxygen vacancies increase, and the catalytic performance decreases.
[0058] Comparative Example 4
[0059] The difference from Example 4 is that the amounts of Ce(NO3)2·6H2O and Ni(NO3)2·6H2O are adjusted to 1 g and 7.3670 g respectively, ensuring that the molar ratio of nickel salt to cerium salt is 11:1. The other aspects are the same as those of Example 4, and Ni 11 Ce1 catalyst.
[0060] The Ni obtained in this comparative example 11 There is a large amount of agglomerated nickel oxide in the Ce1 catalyst. The agglomerated particles are easy to sinter, and the catalytic performance decreases.
[0061] Performance testing:
[0062] Catalytic activity test of catalyst: The catalysts obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were used in the water gas shift reaction. The water gas shift reaction was carried out in a fixed bed reaction. The specific process was as follows: 100 mg of catalyst and 100 mg of quartz sand were weighed, and H2 / Ar (50 / 50, v / v) (60 mL / min) was introduced at normal pressure and 500°C for reduction for 1 hour, and then a mixed gas consisting of CO, water and nitrogen with a volume ratio of 2:10:88 was introduced to test the catalyst performance. The reaction temperature was 150 to 400°C, and the feed space velocity was 42000 h -1 , the results are as follows Figure 3 shown.
[0063] Figure 3 The figure is a relationship between the catalytic activity of the catalysts obtained in Examples 1 to 5 and Comparative Examples 1 to 2, that is, the CO conversion rate, and the temperature. Figure 3 It can be seen that with the increase of the nickel-cerium molar ratio in the reversed structure nickel-based catalyst, the activity of the reversed structure nickel-based catalyst gradually increases. When the nickel-cerium molar ratio is 9:1, the temperature required for complete conversion of CO is the lowest, and the activity of the reversed structure nickel-based catalyst is the best. At 250°C, the conversion rate of CO reached 100%. The activity of pure nickel oxide and pure ceria catalysts is not as good as that of the reversed structure catalyst, which proves that the reversed structure can significantly improve the ability of the catalyst to remove CO in the water gas shift reaction.
[0064] Catalytic stability and service life test of catalyst: The catalyst obtained in Example 5 was used in the water vapor shift reaction. The water vapor shift reaction was carried out in a fixed bed reaction. The specific process was as follows: 100 mg of catalyst and 100 mg of quartz sand were weighed, and H2 / Ar (50 / 50, v / v) (60 mL / min) was introduced at normal pressure and 500°C for reduction for 1 hour, and then a mixed gas consisting of CO, water and nitrogen with a volume ratio of 2:10:88 was introduced to test the catalyst performance. The reaction temperature was 300°C and the feed space velocity was 42000 h -1 , sustained response, the results are as follows Figure 4 shown.
[0065] Figure 4 The stability evaluation of the catalyst obtained in Example 5 is a graph showing the relationship between the CO conversion rate and the catalytic time. Figure 4 It can be seen that the reverse-phase structure nickel-based catalyst obtained in Example 5 can achieve a CO conversion rate of more than 95% within 50 hours, and has the characteristics of high stability and long service life.
[0066] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0067] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a reverse phase structure nickel-based catalyst for water gas shift reaction, characterized in that: The steps include: Mixing cerium salt, nickel salt, promoter and water to obtain a mixed solution; subjecting the mixed solution to hydrothermal treatment and drying in sequence to obtain a solid product; calcining the solid product to obtain the reverse phase structure nickel-based catalyst; The promoter includes one or more of ethylene glycol, acetic acid, propionic acid and ethanol.
2. The method for preparing the reverse phase structure nickel-based catalyst for water gas shift reaction according to claim 1, characterized in that: The cerium salt includes cerium nitrate and / or cerium acetate; the nickel salt includes nickel nitrate and / or nickel acetate.
3. The method for preparing the reverse phase structure nickel-based catalyst for water gas shift reaction according to claim 1, characterized in that: The molar ratio of the cerium salt to the nickel salt is 1-9:1-9; the concentration of the cerium salt in the mixed solution is 6.32-75.94 g / L; and the volume ratio of the accelerator to water is 15-16:0.5-1.
4. The method for preparing the reverse phase structure nickel-based catalyst for water gas shift reaction according to claim 1, characterized in that: The temperature of the hydrothermal treatment is 170-190° C., and the time of the hydrothermal treatment is 5-7 hours.
5. The method for preparing the reverse phase structure nickel-based catalyst for water gas shift reaction according to claim 1, characterized in that: The drying time is 11 to 13 hours.
6. The method for preparing the reverse phase structure nickel-based catalyst for water gas shift reaction according to claim 1, characterized in that: The calcination temperature is 480-520° C., the calcination time is 3.5-4.5 hours, and the calcination heating rate is 8-12° C. / min.
7. The inverse structure nickel-based catalyst prepared by the method for preparing the inverse structure nickel-based catalyst for water gas shift reaction according to any one of claims 1 to 6.
8. Use of the reverse phase structure nickel-based catalyst according to claim 7 in water vapor exchange reaction.
9. The use of the reverse phase structure nickel-based catalyst in water vapor exchange reaction according to claim 8, characterized in that: The reaction conditions of the water vapor exchange reaction are: the temperature is 150-400°C, the reaction gas is a mixed gas composed of CO, water and inert gas, and the feed space velocity of the mixed gas is 41000-43000h -1 .
10. The use of the reverse phase structure nickel-based catalyst in water vapor exchange reaction according to claim 8, characterized in that: The reversed-phase nickel-based catalyst is subjected to reduction treatment before the water vapor exchange reaction; The reduction treatment includes: reducing the reverse structure nickel-based catalyst with a mixed gas of H2 and Ar; the volume proportion of H2 in the mixed gas of H2 and Ar is 10-50%; the temperature of the reduction treatment is 450-550°C, and the time of the reduction treatment is 1-1.5h.
Citation Information
Cited By
Reverse-phase nickel-based catalyst as well as preparation method and application thereof
CN121869379A